2011
DOI: 10.1007/s00127-011-0388-2
|View full text |Cite
|
Sign up to set email alerts
|

Service user attachments to psychiatric key workers and teams

Abstract: Strong correlations among the self-reported PAM scales suggest that self-reported attachment in specific therapeutic relationships is consistent with self-reported attachment in general relationships. The self-ratings were not consistently correlated with informant-ratings and team informant ratings were particularly poorly correlated with self-ratings. This suggests that it is vital that teams consult service users themselves when making decisions about their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…There were 21 papers describing 20 studies that met the inclusion criteria for this review: Arbuckle, Berry, Taylor & Kennedy ; Berry, Barrowclough & Wearden ; Berry, Wearden, Barrowclough, Oakland & Bradley ; Blackburn, Berry & Cohen ; Couture Lecomte & Leclerc ; Dozier ; Dozier, Cue & Barnett ; Dozier & Lee ; Dozier, Lomax, Tyrrell & Lee ; Dozier, Stevenson, Lee & Velligan ; Kvrgic, Beck, Calvelti, Kossowsky, Stieglitz & Vauth ; MacBeth, Gumley & Schwannaeur ; Mulligan & Lavender ; Picken, Berry, Tarrier & Barrowclough ; Ponizovsky, Nechamkin & Rosca ; Ponizovsky, Vitenberg, Baumgarten‐Katz & Grinshpoon ; Tait, Birchwood & Trower ; Tyrrell, Dozier, Teague & Fallot ; Quijada, Tizon, Artigue, Kwapil & Barrantes‐Vidal ; Owens, Haddock & Berry and Kvrgic, Cavelti, Beck, Rusch & Vaulth . Table provides a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 21 papers describing 20 studies that met the inclusion criteria for this review: Arbuckle, Berry, Taylor & Kennedy ; Berry, Barrowclough & Wearden ; Berry, Wearden, Barrowclough, Oakland & Bradley ; Blackburn, Berry & Cohen ; Couture Lecomte & Leclerc ; Dozier ; Dozier, Cue & Barnett ; Dozier & Lee ; Dozier, Lomax, Tyrrell & Lee ; Dozier, Stevenson, Lee & Velligan ; Kvrgic, Beck, Calvelti, Kossowsky, Stieglitz & Vauth ; MacBeth, Gumley & Schwannaeur ; Mulligan & Lavender ; Picken, Berry, Tarrier & Barrowclough ; Ponizovsky, Nechamkin & Rosca ; Ponizovsky, Vitenberg, Baumgarten‐Katz & Grinshpoon ; Tait, Birchwood & Trower ; Tyrrell, Dozier, Teague & Fallot ; Quijada, Tizon, Artigue, Kwapil & Barrantes‐Vidal ; Owens, Haddock & Berry and Kvrgic, Cavelti, Beck, Rusch & Vaulth . Table provides a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…No data regarding gender were provided for 42 participants (3.2%) . The inclusion or exclusion criteria were not explicitly stated for eight studies .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Arbuckle et al . () and Catty et al . () found that the relationship between a service user and a key worker was central to service users' connection with their CMHT.…”
Section: Building Relationships Through Participation In Carementioning
confidence: 85%
“…Commonly, studies reported on the importance of building relationships between service users and service providers in order to meet service users' needs and expectations (Arbuckle et al . n = 24, Catty et al . n = 93, Gale et al .…”
Section: Building Relationships Through Participation In Carementioning
confidence: 99%
“…others and social withdrawal; both of which have been implicated in cognitive models of paranoia (Freeman et al, 2002). Previous studies have reported associations between avoidant attachment and hallucinations (Ponizovsky et al, 2013;Dozier, 1990;Arbucke et al, 2012). Previous research has also found evidence of associations between avoidant attachment and critical and threatening themes in voice hearing and it has recently been proposed that attachment theory may advance our understanding of the mechanisms underlying distressing voices and help to explain well-established associations between interpersonal traumas and voice-hearing (Read and Gumley, 2008;Longden et al, 2012).…”
Section: Main Findingsmentioning
confidence: 98%